Research advances on the influence of typical geochemical and hydrogeological characteristics on the natural attenuation of pollutants - Meng Zhao; Yonghai Jiang; Fan Feng; Yongfeng Jia; Xinying Lian; Changjian Shang; Yongge Zang (地质科技通报, 2023)
As an effective risk prevention and control tool for contaminated sites, Monitoring Natural Attenuation (MNA) has been applied worldwide. The core of this technology is to determine the ability and efficiency of pollutant attenuation, which are influenced by the nature of the pollutants themselves, as well as the typical geochemical and hydrogeological conditions and other inherent characteristics of the site. It is of greater practical importance to clarify the influence of the inherent properties of the site on the natural attenuation of pollutants for the rational application of the technology. The authors address the influence of typical site geochemical characteristics and hydrogeological characteristics on the natural attenuation process of pollutants in groundwater and its mechanism. The typical geochemical characteristics, such as the organic matter and mineral composition of sediments, control the adsorption and complexation behavior of pollutants, and participate in the electron transfer process to influence the biodegradation and chemical transformation of pollutants. Hydrogeological characteristics influence the ability of natural attenuation through the differences in permeability, adsorption and desorption capacity caused by the lithologic characteristics of sediments. Groundwater flow rate controls the convection and dispersion of pollutants and affects the dissolution and release of pollutants from sediment to groundwater as well as the kinetic process of biodegradation. In general, due to the complexity of organic matter, mineral and microbial components and the heterogeneity of hydrogeological conditions, the study of the influence of site intrinsic properties on the natural attenuation of pollutants needs to be further strengthened. In particular, we need to identify the spatial and temporal dynamics of pollutant attenuation through long-term site monitoring, and deepen the understanding of the mechanisms underlying the interaction between typical site geochemistry, hydrogeological conditions and pollutants.